Research review of adaptive reclosure in transmission lines - Liang, Zhen-Feng; Suonan, Jia-Le; Song, Guo-Bing; Kang, Xiao-Ning (Dianli Xitong Baohu yu Kongzhi, 2013)
It is important to study adaptive reclosure which can improve the success rate of reclsosure and avoid reclosing to the fault lines because of defects of conventional auto-reclosure. This paper discusses the conception of transient fault and permanent fault, and distinguishes them based on whether the fault point current is zero. It is pointed out that the success of auto-reclosure is not only decided by fault character, but also is influenced by reclosing time sequence. So the adaptive reclosure should contain both distinguishing permanent faults from transient faults and optimization of reclosing time sequence. The single-phase adaptive reclosure, the three-phase reclosure and the adaptive reclosure for double circuits are respectively reviewed. The prospects in adaptive reclosure are described.